The effect of performance and corporate governance to risk disclosure among listed companies in Malaysia / Ag Kaifah Riyard Kiflee and Mohd Noor Azli Ali Khan - Kiflee, Ag Kaifah Riyard; Ali Khan, Mohd Noor Azli (Accounting Research Institute (ARI), UiTM Shah Alam, 2021)
The objective of this study was to determine the presence of risk information within the annual report of Malaysian non-financial listed companies and empirically extend the current literature of corporate governance and risk disclosure by incorporating an interaction effect in the model. The study found that listed companies in Malaysia experienced a positive upward trend in terms of risk disclosure practice for 10 years (2008-2017). A total of 166 companies were randomly extracted from Main Board of Bursa Malaysia from 2008 to 2017. This study used content analysis, descriptive statistics and multiple regression to explain the relationship between corporate governance and risk disclosure with the effect of the interaction variable. The study also found positive and significant relationship between board independence, board size and board gender with risk disclosure practice. It is also revealed that attainment discrepancies positively influence the relationship between corporate governance and risk disclosure practices among listed companies in Malaysia.